Strengthening Religious Character In Madrasah: Integrating Pesantren Values As An Educational Strategy - Achmad Zuhri; Abdurrahman Mas'ud; Fatah syukur (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This study explores the strengthening of religious character in madrasah through the integration of pesantren value systems. This approach aims to help students understand, care about, and practice religious values in their daily lives. The study employs a qualitative method conducted in four Madrasah Ibtidaiyyah in Kudus. Data were collected through observations, interviews, and documentation, then analyzed in depth. The findings indicate that understanding religious values can be reinforced through pesantren literacy, which is rich in religious values. The formation of religious character is carried out through religious traditions, role modeling, and the internalization of values, ultimately leading to moral action. These actions are classified into three aspects of spiritual strength: faith (iman), Islam, and excellence (ihsan). A strong religious character will naturally develop when a religious culture is established in the madrasah environment, making religious values an integral part of students' livesKeywords: Strengthening Religious Character, Pesantren Values, Madrasah, and Religious Culture